2011
DOI: 10.1111/j.1755-0238.2011.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the analysis of smoke related phenols and their conjugates in grapes and wine

Abstract: Background and Aims: Australian grape growers and winemakers have typically relied on guaiacol and 4-methylguaiacol measurements to determine smoke exposure of grapes following bushfires or prescribed burns. However, the guaiacol and 4-methylguaiacol content of grapes does not always correlate with the extent of taint in resultant wines. This study compared several methods for the analysis of smoke related phenols and their conjugates in grapes and wine, to determine their capacity as diagnostic assays for smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 18 publications
3
61
0
1
Order By: Relevance
“…Each fuel type was (1) reconstituted in proportion to biomass components that burn in a decadal fire event and (2) pyrolysed under conditions that reproduce wildfire temperature profiles (Gould et al, 2007). Recent work has shown that, at least in young wines, the putative smoke taint compounds are predominantly sequestered as glycoconjugates and only a small proportion is present as volatile phenols (Hayasaka, Baldock, Parker et al, 2010;Kennison et al, 2008;Singh et al, 2011, in press;Wilkinson et al, 2011). Thus, in this study both volatile and glycoside-bound phenols were considered.…”
Section: Introductionmentioning
confidence: 95%
“…Each fuel type was (1) reconstituted in proportion to biomass components that burn in a decadal fire event and (2) pyrolysed under conditions that reproduce wildfire temperature profiles (Gould et al, 2007). Recent work has shown that, at least in young wines, the putative smoke taint compounds are predominantly sequestered as glycoconjugates and only a small proportion is present as volatile phenols (Hayasaka, Baldock, Parker et al, 2010;Kennison et al, 2008;Singh et al, 2011, in press;Wilkinson et al, 2011). Thus, in this study both volatile and glycoside-bound phenols were considered.…”
Section: Introductionmentioning
confidence: 95%
“…Wines from the earlier vintage therefore spent more than a year in storage. Other workers have suggested that tests for smoke compounds should include the testing of glycoconjugated VP precursors in order to better predict taint potential (Dungey et al, 2011;Wilkinson et al, 2011;Parker et al, 2012). In this study, differences in guaiacol concentration were not significantly different over the two vintages.…”
Section: Discussionmentioning
confidence: 46%
“…The smoke was produced by burning fynbos mixed with other vegetation in order to simulate smoke that might be generated by veld fires. Wines made from the smoke-affected grapes were then subjected to VP analysis by HS-SPME GC-MS, using a method adapted from Wilkinson et al (2011) and Singh et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Responding to the need to more reliably quantify the diversity of volatile phenol aglycones and glycoconjugated, and hence aid prediction of the degree of contamination of wine with smoke taint, Wilkinson et al (2011) compared recently published analytical methods. Strong correlations were found between the amounts of guaiacol and 4-methylguaiacol glycoconjugates and the aglycones released through hydrolysis.…”
Section: Research To Datementioning
confidence: 99%